2016
DOI: 10.15448/1980-6523.2016.2.15324
|View full text |Cite
|
Sign up to set email alerts
|

Surface roughness influences Candida albicans biofilm formation on denture materials

Abstract: Objective: This study aimed to evaluate the influences of surface roughness (SR) of denture base and liner materials on Candida albicans biofilm formation. Methods: Discs were fabricated using poly (methyl methacrylate) acrylic resin and poly(ethyl methacrylate) denture liner, according to manufacturers' instructions. Both acrylic resin and relined discs were finished or finished + polished and the SR was measured. Discs were saliva-coated, and C. albicans biofilms were developed on such surfaces for 48 hours.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Rough films have more cavities and a larger surface area than films with a smooth surface, which promotes the absorption of water, decreasing the contact angle . Surfaces with higher roughness also tend to favor the adherence of microorganisms, because they increase the available surface area and promote their protection in these spaces, being a relevant criterion in the characterization of materials with bactericidal and fungicide proposals …”
Section: Resultsmentioning
confidence: 99%
“…Rough films have more cavities and a larger surface area than films with a smooth surface, which promotes the absorption of water, decreasing the contact angle . Surfaces with higher roughness also tend to favor the adherence of microorganisms, because they increase the available surface area and promote their protection in these spaces, being a relevant criterion in the characterization of materials with bactericidal and fungicide proposals …”
Section: Resultsmentioning
confidence: 99%
“…There have been many studies showing positive correlation between the surface roughness and deposition of pathogenic microorganisms on the material’s surface [ 22 , 34 , 35 ]. The larger the development of the surface and the larger number of natural niches for microorganisms, the greater the potential for the deposition of C. albicans.…”
Section: Resultsmentioning
confidence: 99%
“…Abuzar et al suggested that the standard surface roughness of PMMA denture base material should be no more than 0.2 µm. Da Silva et al reported that a lower surface roughness value can reduce C. albicans biofilm accumulation on PMMA. As shown in Figure , the titanium peak can still be detected by XPS after 6000 cycles of brushing and 5 months of water storage.…”
Section: Discussionmentioning
confidence: 99%